IMPLEMENTASI BATHSUL MASA’IL DALAM MENINGKATKAN KEMAMPUAN SANTRI MENJAWAB BERBAGAI PERMASALAHAN DI MASYARAKAT - Eko Prasetiyo; Syaiful Hanif; Afifah Puri Rahmawati (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2022)
ABSTRACT This study aims to determine the implementation of bathsul masa'il in PP. Arbai Qohhar Jambangan Ngawi and the ability of students to answer various problems in society through bathsul masa'il. This study uses a type of field research (field research) which is descriptive qualitative. The data sources in this study are divided into two, namely primary data (main data) and secondary data. Sources of data are determined by direct appointment of informants who can provide valid and accurate information regarding the topic being researched. While the data collection method or research instrument using observation, interviews and documentation. The data analysis used in this research is data reduction, data presentation, and conclusion drawing/verification. the results of the study show that: (1) Bathsul masa'il can be interpreted as a discussion of several problems that refer to the problem of fiqh. Actually, bathsul masa'il is not much different from deliberation or discussion, it's just that in bathsul masa'il there are people who have different roles and tasks that are not in deliberation or discussion activities, such as moderators, sails, drafting teams, and mushohih. (2) Bathsul masa'il activities in PP. Arbai Qohhar Jambangan Paron Ngawi is a routine activity once a month, to be precise every Sunday night at the beginning of the month. This activity was carried out in the foyer of the cottage mosque. (3) The process of bathsul masa'il activities in PP. Arbai Qohhar is going well. The implementation of this bathsul masa'il goes through various stages, namely: opening, tashowwur problems, delivery of answers, categories of answers, argumentative debates, enlightenment of references, formulation of answers, and ratification. The students of Pondok Arbai Qohhar proved to be able to answer problems through bathsul masa'il. Key Words: Bathsul masa'il, the ability of students, community challenges